Structural Change in MENA Remittance Flows - George S. Naufal; Ismail H. Genc (Institute for the Study of Labor (IZA), 2013)
After independence, the GCC countries relied heavily on foreign workers from fellow Arab countries. Thus, remittances flowed from GCC to other countries in MENA. In the 1980s-1990s labor source switched to South Asia; so did the flow of remittances. This paper examines the consequences of the shift in the source of labor by econometrically testing the existence of structural breaks in the flow of remittances in the MENA region. The change in the direction of remittance flows deprived several MENA labor exporters of large sums of foreign exchange, adding significant economic, social and political hardships on non-GCC MENA countries.
Keywords: F16; F22; F24; C22; 330; migration; remittances; unit roots; structural break; Gulf Cooperation Council (GCC); Middle East and North Africa (MENA)